The compaison of the efficacy of cyproterone acetate and castration monotherapies in metastatic prostate cancer: A multicenter study of Turkish uro-oncology group. - BEKİROĞLU, GÜLNAZ NURAL (My University, 2007)
Objective: To detect the therapeutic efficacy of CPA and to compare it with surgical or medical castration in advanced prostate cancer Patients and Methods: Patients from 19 Urology Centers with prostate adenocarcinoma of stages T1- 4N+MX or T1-4NXM+ were enrolled. A total of 120 patients were randomized to receive CPA 3X100mg/d(Group 1) versus medical or surgical castration(Group 2).The primary endpoints for this trial were overall and disease-spesific survival.Progression-free survival(PSA progression time) and testosterone decrease rate were assessed as secondary endpoints.Progression-free survival probabilities were calculated by the Kaplan-Meier method and comparison of survival probabilities was performed by the Logrank test. Results: The median PSA values were 42ng/dl in both groups at initiation and decreased to 3.0 and 2.1 respectively in 3 months(p>0.05).Castrate testosterone levels were reached in two groups after 3 months therapy( 9% and 6.7% of initial values respectively;p>0.05).The data is immature to assess the survival durations,but in median follow-up of 24 months,no difference in regard to PSA-progression was detected in the two groups(p=0.616). Conclusion: This randomized study of CPA and castration in patients with metastatic prostate cancer has not so far revealed any significant differences in progression-free survival.The initial efficacy and tolerability of monotherapy encourages us to comment that this therapy is safe and acceptable. Keywords: Prostate cancer,Cyproterone acetate,Castration,PSA-progression,Survival

Amaç: İlerlemiş prostat kanserinde tibbi veya cerrahi kastrasyon ile CPA’yi karşılatırmak ve CPA’nin terapötik etkisini ortaya koymak. Gereç ve Yöntem: Ondokuz Üroloji Merkezi’ne başvuran T1-4N+MX veya T1-4NXM+ evreli prostat adenokanserli hastalar çalışmaya alınmıştır. Toplam 120 hasta, CPA 3X100mg/gün (Grup1) ve tıbbi veya cerrahi kastarasyon (Grup 2) gruplarına rastgele dağıtılmışlardır. Bu denemenin birincil son noktaları genel ve hastalığa-özel sağkalım olasılıklarıdır. Progresyonsuz sağkalım (PSA progresyon zamanı) ve testesteron düşüş hızı ikincil son noktalar olarak kabul edilmiştir.Progresyonsuz sağkalım olasılıkları Kaplan-Meier metoduyla hesaplanmış ve Logrank testiyle de sağkalım olasılıkları karşılaştırılmıştır. Bulgular: Başlangıçta her iki grupta da PSA ortanca(medyan) değerleri 42ng/dl bulunmuş ve 3 ayda Grup1’de 3.0 ‘e Grup2’de de 2.1’e düşmüştür (p>0.05). Her iki grupta da 3 aylık bir tedavi sonrasındaki testesteron seviyeleri başlangıçtaki değerlerin Grup1’de % 9’una Grup2’de %6.7’sine ulaşmıştır (p>0.05).Her ne kadar veriler sağkalım süreleri için tam olmasa bile, ortanca 24 aylık izlem süresinde PSAprogresyonu için iki grup sağkalımlarında bir fark bulunmamıştır (p=0.616). Sonuç: Yaptığımız bu randomize çalışma, CPA ve kastrasyon tedavisi alan prostat kanserli hastalarda progresyonsuz sağkalım bakımından 24 aylık izlem zarfında herhangi bir anlamlı faklılık ortaya koymamıştır. Monoterapinin başlangıçtaki etkinliği ve tolerabl olması bu terapinin kabul edilebilir ve güvenilir bir tedavi olduğu yorumlarında bizi cesaretlendirmektedir. Anahtar Kelimeler: Prostat kanseri,CPA,Kastrasyon,PSA-progresyon,Sağkalım
Metastati̇k prostat kanseri̇nde cyproterone acetate ve Kastrasyon monoterapi̇leri̇ni̇n etki̇nli̇ğini̇n karşilaştırması: çok Merkezli̇ bi̇r türk üro-onkoloji̇ grubu çalişmasi
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyoistatistik ve Tıp Bilişimi; Cerrahi Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Biostatistics and Medical Informatics; Surgery Medicine Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; TIBBİ BİLİŞİM; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; MEDICAL INFORMATICS; MEDICINE, GENERAL & INTERNAL; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Cerrahi; Dahiliye; Tıbbi Bilişim; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Surgery; Internal Medicine; Health Informatics; Family Practice; Medicine (miscellaneous); General Medicine; Prostat kanseri; CPA; Kastrasyon; PSA-progresyon; Sağkalım; Prostate cancer; Cyproterone acetate; Castration; PSA-progression; Survival